Launch of the 2024 Breakthrough Agenda Report: Agriculture - CGIAR (CGIAR, 2024)
The Breakthrough Agenda was launched by 45 world leaders at the UN Climate Change Conference (COP26) in 2021 and is a commitment to work together to accelerate innovation and the deployment of clean technologies, making them accessible and affordable for all by 2030.